STRATEGI KEHUMASAN PEMERINTAH DAERAH DALAM PENGEMBANGAN PARIWISATA WADUK JATIGEDE KABUPATEN SUMEDANG - Kuswandi, Aos; Nuraini, Siti; Al Rasyid, M. Harun; Hartono, Rina Susanti (Jurnal Agregasi, 2022)
This article discusses about Local government's public relations strategy in socializing the new tourism development of Jatigede Dam in Sumedang Regency. The method used in research is qualitative methods. Data collecting techniques through observation, in-depth interviews and documentation collection. Research informants were determined purposively from elements of local government, community groups, tourism business actors, and tourists. The results of the study concluded that the local government public relations strategy in developing tourism in the Jatigede Dam was carried out through several types of strategies. The programs have been implemented well but still need to be improved again to increase the number of tourists.